Mobile Energy-Storage Technology in Power Grid: A Review of Models and Applications - Lu, Zhuoxin; Xu, Xiaoyuan; Yan, Zheng; Han, Dong; Xia, Shiwei (Sustainability, 2024)
In the high-renewable penetrated power grid, mobile energy-storage systems (MESSs) enhance power grids’ security and economic operation by using their flexible spatiotemporal energy scheduling ability. It is a crucial flexible scheduling resource for realizing large-scale renewable energy consumption in the power system. However, the spatiotemporal regulation of MESS is affected by the complex operating environments in the power and transportation networks. Numerous challenges exist in modeling and decision-making processes, such as incorporating uncertainty into the optimization model and handling a considerable quantity of integer decision variables. This paper provides a systematic review of MESS technology in the power grid. The basic modeling methods of MESS in the coupled transportation and power network are introduced. This study provides a detailed analysis of mobility modeling approaches, highlighting their impact on the accuracy and efficiency of MESS optimization scheduling. The applications of MESS in the power grid are presented, including the MESS planning, operation, and business model. The key challenges encountered by MESS in power grid operations across various scenarios are analyzed. The corresponding modeling methods, solution algorithms, and typical demonstration projects are summarized. At last, this study also proposes the MESS system research and application prospects based on the consideration of its promotion.